Copper-boryl mediated transfer hydrogenation of N-sulfonyl imines using methanol as the hydrogen donor. (9th April 2021) - He, Yi; Li, Shi-Guang; Mbaezue, Ifenna I.; Reddy, Angula C.S.; Tsantrizos, Youla S.
Abstract: B2 Pin2 -assisted copper-catalyzed transfer hydrogenation of aromatic sulfonylimines has been achieved, delivering a variety of aryl/heteroaryl sulfonamides in good to excellent yields under mild reaction conditions and with methanol as the hydrogen source. Mechanistic studies suggest that the reaction may proceed via a transient α-borylated intermediate, followed by protodeboration to afford the sulfonamide products. Graphical abstract: Image 1 Highlights: Copper-mediated catalysis. Transfer hydrogenation. Aryl sulfonamides. Heteroaryl sulfonamides.